A CRITICAL EVALUATION OF TONY BLAIR’S LABOUR GOVERNMENT’S POLICIES TOWARDS EUROPEAN UNION - P. S., Balasubramanya (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper mainly explains the United Kingdom and European Union relations during Tony Blair’s period. After UK’s membership to the EU in 1973, it had not actively engaged in the European Union’s policy initiatives and implementation process. From 1973 to 1996, the successive UK Prime Ministers followed a negative and sceptical attitude towards various EU policy initiatives and none of the UK Prime Ministers showed any special interest in improving its relations with the EU. At this juncture, Tony Blair’s Labour government made a huge difference in the European Union and United Kingdom’s relationship. In this context, the study of Tony Blair’s New Labour government’s policies and perspectives towards the European Union gives a better understanding of the United Kingdom and European Union’s relations during that period.